Multilevel evaluation of the Cagayan State Trade Extension Program - Maguigad, Celiaflor Acebedo (1992)
This study was conducted to assess the Multilevel Evaluation of the CSU Trade Extension Program. Specifically, it sought to determine the level of understanding and internalization of IRD among the policymakers, middle-level managers and implementors in the decision and implementation areas of: a) authority functions, duties and responsibilities: b) organizational set-up: c) staffing : and d) resources allocation/budgeting: to identify the conceptualization of IRD implemented in the Trade Extension Program before and after the adaptation of IRD policies; to determine the effects of the program to the trainees; and to determine the problems met in the Trade Extension Program.
Triangulation method was used in the study. A group of 117 trade extension trainees; 19 director/campus dean, 31 extension coordinators/traitors were randomly selected served as the trade extension samples of the study. Instruments designed to gather they needed information were questionnaires and interview schedule. In addition, documentary analysis and actual observation in the extension sites were made. To describe and categorized the variables, frequency, counts, mean standard deviation, percentage and rank were used. The hypothesis was tested by using the T-test for correlated and uncorrelated samples.
The research revealed that the policymakers, middle-level managers and implementors have common understanding on their authority, functions, duties and responsibilities, of the organization set-up, staffing and budgeting. The Philosophy of integrated rural development was clearly integrated in the formulation of trade extension goals, trade extension curriculum, but not in the delivery system. Coordination among other agencies with similar purposes of improving the rural sector was not successfully tapped. There were slight differences in the trade extension programs methods and strategies, and equipment used before and after the philosophy of integrated rural development was adopted. Instruction was more individualized and more equipment were acquired.
The trade extension program was successfully provided the trainees usable trade skills in dressmaking, food trades, automotive/driving, and practical electricity. These trade skills have been used by trainees to put up a business and as sideline.
Slow processing of requisitions/purchase orders, delayed release of funds and poor attendance of extension personnel during meetings have brought about partial implementation of the program and the partial attainment of the program goals and objectives. Lack of capital poses the greatest problem to some of the trainees. Without capital, they could hardly procure the equipment and supplies needed in setting up projects to use their trade skills.

On the basis of the finding conclusions, the following are recommended:

1. The decisions and actions of the policymakers, middle-level managers should be more coordinated and directed to fully implement the trade extension program. Decisions and actions should strive towards-
a. providing for more logistic support by timely release of funds, timely procurement of adequate equipment and supplies, timely delivered of these procurements at the training sites.
b. improving the pay and other financial benefits of the extension personnel to enhance their effectiveness and efficiency. More rationale and just honoraria and service credits be conceived to compensate.
c. designing a mechanism to monitor and evaluate the program in all phases on stages to provide baseline and feedback data to guide the delivery and services. Among others, data on budget expenditures, requisitions, consumptions or use, problems encountered could be part of the information bank.
d. linking the trade extension program with agricultural extension program in order to develop competencies in selling up small-state agro-industrial projects.
e. giving permanent status to extension personnel to give them security of tenure.

2. Trainees should be assisted in organizing themselves into cooperatives to make them avail of government support, especially credit facilities. Giving them financial support to initiate income-generating projects along with their trade skills would make them productive members of society; eventually, they would contribute to the development of their communities.
3. Other technology delivery system appropriate for the development of trade skills should be tried out, whatever is found most effective to trade skills development should be used and shared to other agencies.
4. A linkage mechanism among agencies with similar goals of the trade extension program should be devised. A systematic coordination among these agencies could be reached through the concreted efforts of the heads of agencies. Efforts should be coordinated in order that each agency’s involved should ensure the development of functional, self-reliant and self-sufficient human resource. These could be done through the initiation of economical means of providing the development of job competencies to the least privileged so that the objectives of the program will be achieved quantitatively and qualitatively.
5. The placement/employment office of the University should be tapped to act as facilitator for training graduates in seeking jobs in industries. By this way, trainees who could not put up their own business could be assisted in finding a job.
6. Similar studies should conduct on trade extension, with focus on which delivery system is best for particular skills to a group of clientele.
Computer print-out
Thesis (Ph.D.)--University of the Philippines, Diliman.
Thesis
Keywords: Cagayan State University Trade Extension Program; University extension -- Philippines